Perancangan Sistem Presensi Online dan Penggajian Karyawan Berbasis Mobile - Valentino Lim (LKP KARYA PRIMA KURSUS, 2026)
Rapid advancements in information technology have significantly improved work systems and human resource management, especially in the areas of attendance tracking and payroll processing. Viva Shops, a retail store specializing in kitchenware and cleaning supplies, still uses manual procedures through Google Spreadsheets to record employee attendance and calculate salaries, which is inefficient, prone to errors, and unable to effectively monitor workers outside the store area. This study aims to design a mobile-based attendance and payroll system that streamlines the recording of employee presence while automating wage calculations. The application is developed using the Flutter framework with Supabase Realtime Database, and includes key features such as geolocation-based online attendance, real-time photo capture, leave and permission submissions, and automatic calculation of total working hours and employee wages. Using the Waterfall development model, which consists of requirement analysis, design, and implementation, the resulting system improves efficiency and accuracy in real-time attendance tracking and payroll processing, enabling store owners to more effectively monitor employee activity and manage workforce data in an integrated manner.